IMPLEMENTATION OF BALANCED SCORECARD IN BUDGET PREPARATION - listiadi, agung; RakhmawatiDwi Yuli Rakhmawati; Meylia Elizabeth Ranu; Raya Sulistyowati (International Economic Conference of Business and Accounting, 2025)
The Balanced Scorecard concept developed in line with the development of the implementation of the concept. Balanced Scorecard in the early stages of its experiment, the Balanced Scorecard was a scorecard used to record the results of executive performance scores. The results of this comparison are used to evaluate executive performance. The word balanced is intended to indicate that executive performance is measured in a balanced manner from two perspectives: financial and non-financial, short-term and long-term, internal and external. In further developments, the Balanced Scorecard is not only related to the card used to measure executive performance. The Balanced Scorecard is more utilized as an executive tool for strategic planning, namely as a tool to translate the mission, vision, goals, basic beliefs, basic values ​​and organizational strategies into a comprehensive, coherent, measurable and balanced action plan.